Platelet Count and Its Prognostic Value in Pregnancy Induced Hypertension - Sharma, Nirmala; Kumari, Sheela; BC, Durga; Shrestha, Merina (Journal of Nepalgunj Medical College, 2020)
Introduction: Hypertensive disorders of pregnancy is one of the maternal diseases that cause the most detrimental effects to the mother and the fetus.1 It is the leading cause of direct maternal death along with hemorrhage and infections. Approximately 70% of hypertensive disorders are due to gestational hypertension, preeclampsia and eclampsia whereas other 30% are due to preexisting or undiagnosed hypertension.2 Out of all the hematological abnormalities that occur in PIH, thrombocytopenia is the most common seen to occur in 11% to 29% of patients.3 Thrombocytopenia occurs more commonly in patients with eclampsia (30%) compared to patients with both mild and severe forms of pre-eclampsia (15%-18%).4 Aims :To find out the severity of disease with platelet count in pregnancy induced hypertension. Methods: This is a hospital- based descriptive cross sectional study, conducted in the department of Obstetrics and Gynecology at Nepalgunj Medical College Teaching Hospital, Kohalpur, Banke, Nepal, conducted over a period of one year from September 2018 to August 2019. Fifty pregnant women were enrolled in study after getting informed written consent and assessing for inclusion and exclusion criteria. Results: Incidence of Pre-eclampsia/eclampsia is 2.3% in this study. Majority of the women belong to age group 21-25(40%), followed by 15-20(38%) with mean age 23.18±5.45. 62% constituted primigravidas and 38% were multigravidas. 33 (66%) cases were at term (37-42 weeks of gestation), 11(22%) at 34-36 weeks of gestation and 6 (12%) were at 28-33 weeks of gestation with mean gestational age 36.38±3.17. Eclampsia cases were found more i.e. 48%, followed by pre-eclampsia 38% and Gestational hypertension 14%. Moderately low platelet count was seen in 11.76% of Gestational hypertension, 47% of pre-eclampsia and 41.17% of eclampsia and severely low platelet count in 21.4% pre-eclampsia and 64.70% of eclampsia. Conclusion: PIH continues to be a leading cause of Maternal and perinatal morbidity and Mortality. The disease accounts of 40,000 maternal deaths worldwide per year5. It is one of the common causes of iatrogenic preterm delivery. Etiology of Pre-eclampsia/Eclampsia is complex and not completely understood. A combination of abnormal Placentation and predisposing maternal factor contribute to widespread endothelial dysfunctions which lead to the syndrome of PIH. To date there has been no screening test that has been widely adopted in clinical practice. Platelet estimation method is reliable, rapid, cheaper, and simple lab method. Prognosis of diseases could be monitored by measuring platelet count and level of platelet count can predict the severity of PIH. Therefore assessment of platelet count has special place in management of PIH.